2016
DOI: 10.1177/0333102416649758
|View full text |Cite
|
Sign up to set email alerts
|

The association between COMT Val158Met polymorphism and migraine risk: A meta-analysis

Abstract: Background The COMT Val158Met polymorphism has long been regarded as a risk factor for migraine. The possible association between COMT Val158Met polymorphism and migraine has been evaluated in several studies, but the results are not consistent. Therefore, we conduct this meta-analysis to address these issues. Methods The WEB OF SCIENCE and EMBASE databases were searched for eligible studies. The odds ratio (OR) with the corresponding 95% confidence interval (CI) was calculated to estimate the strength of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…We did not observe significant differences in the distribution of the Val158Met polymorphism between women with episodic or chronic migraine and healthy women, supporting the assumption that this polymorphism is not involved in a predisposition to suffer from migraine. Our results agree with a recent systematic review concluding that the Val158Met polymorphism was not associated with migraine risk (13). Additionally, Takigawa et al did not also observe differences in the presence of other haplotypes of the COMT gene, e.g., rs4633, rs6267, rs6270 between individuals with migraine and healthy people (14).…”
Section: Val158met Polymorphism and Migrainesupporting
confidence: 92%
See 1 more Smart Citation
“…We did not observe significant differences in the distribution of the Val158Met polymorphism between women with episodic or chronic migraine and healthy women, supporting the assumption that this polymorphism is not involved in a predisposition to suffer from migraine. Our results agree with a recent systematic review concluding that the Val158Met polymorphism was not associated with migraine risk (13). Additionally, Takigawa et al did not also observe differences in the presence of other haplotypes of the COMT gene, e.g., rs4633, rs6267, rs6270 between individuals with migraine and healthy people (14).…”
Section: Val158met Polymorphism and Migrainesupporting
confidence: 92%
“…There are several studies investigating the role of Val158Met polymorphisms in migraine; although the results are inconsistent. The most recent meta-analysis did not observe a significant association between the Val158Met polymorphism and migraine (13). Similarly, a recent study, not included in the abovementioned meta-analysis, did not also reveal differences in Val158Met polymorphism distribution between subjects with migraine and healthy controls (14).…”
Section: Introductionmentioning
confidence: 89%
“…41 Similarly, the rs4680 Val158Met polymorphism has not been either associated to the presence of migraine. 42 The current results are supported by Takigawa et al finding of no significant differences in the presence of other haplotypes of the COMT gene, e.g., rs4633, rs6267, rs6270, between individuals with migraine, TTH or healthy people, 17 supporting that the COMT rs4680 Val158Met polymorphism seems to be not associated to TTH. Nevertheless, since the rs4680 Val158Met polymorphism has been associated, in some studies, to conditions such as fibromyalgia syndrome 43 or temporomandibular pain, 44 it is possible that this genotype may be associated to particular pain conditions rather than to chronic pain syndromes in general.…”
Section: Discussionsupporting
confidence: 80%
“…In this pilot study, which was performed on a small number of patients, no difference was found between the MOH and EM groups, but several genes were identified to change their DNA methylation profile in the chronification in MOH as compared with the controls including COMT (catechol-O-methyltransferase), ZNF234 (zinc finger protein 234), and SOCS1 (suppressor of cytokine signaling 1), which are all involved in the pathogenesis of drug addiction and neuropsychiatric illness. Variability in the COMT gene was associated with migraine, but the two remaining genes did not relate to migraine [74,75]. No difference was found between the MOH and EM groups.…”
Section: Dna Methylation In Migrainementioning
confidence: 99%